ANALYSIS OF USER SATISFACTION OF THE SI SEMAR LAYAK APPLICATION AT THE CLASS I IMMIGRATION OFFICE TPI SEMARANG USING FUZZY SERVICE QUALITY - Galuh Boy Hertantyo; Isidorus Anung prabadhi; Abdullah Muhaimin Hanafi (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
Service quality is a very important factor for service providers in getting customer satisfaction. Improving service quality can be done by fulfilling the wishes expected by customers. A service that is considered to have good quality if the service provided can exceed the expectations of the customer. In this study, we will discuss the analysis of services provided by the Immigration Office Class I TPI Semarang through the SI SEMAR LAYAK application. The method used is Fuzzy Service Quality. From the results of the analysis, the Gap values for each dimension are: Tangible, 1.019; Reliability, 0.840; Responsiveness, 0.889; Assurance, 0.343 and Empathy 0.617 with an average value of 0.741. A positive Gap value indicates that the services provided by the Immigration Office Class I TPI Semarang through the SI SEMAR LAYAK application have been able to exceed the expectations of the applicant.